ANALISIS DETERMINAN HARGA SAHAM BASIC MATERIALS TAHUN 2018-2022 - Delia Septy Dwi Sucahyo; Rahman Amrullah Suwaidi (POLITEKNIK LP3I JAKARTA, 2024)
The research intends to evaluate the impact of leverage ratios, market ratios, and dividend policies on stock prices. All basic materials companies on the Indonesian Stock Exchange until 2022 constitute the research population, then using a purposive sampling method the sample can finally be determined, namely 15 basic materials companies on the Indonesian Stock Exchange during the period 2018 to 2022. Data was collected through documentation techniques referring to annual financial data and historical stock price data and analyzed using multiple regression techniques using SPSS data processing tools. The results of the analysis show that the leverage ratio has no effect on stock prices, while the market ratio and dividend policy have a significant effect on stock prices.